2013
DOI: 10.1158/1940-6207.capr-12-0431
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Urinary PGE-M, a Biomarker of Inflammation, Occur in Association with Obesity, Aging, and Lung Metastases in Patients with Breast Cancer

Abstract: Elevated levels of cyclooxygenase (COX)-derived prostaglandin E2 (PGE2) occur in inflamed tissues. To evaluate the potential links between inflammation and breast cancer, levels of urinary prostaglandin E-metabolite (PGE-M), a stable end metabolite of PGE2, were quantified. We enrolled 400 patients with breast cancer: controls with early breast cancer (n=200), lung metastases (n=100) and metastases to other sites (n=100). Patients completed a questionnaire, provided urine and had measurements of height and wei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 41 publications
(45 reference statements)
1
57
2
Order By: Relevance
“…Previous studies have suggested that the majority of PGE 2 formed in vivo is derived from Cox-2 (24,25). Urinary PGE-M levels in healthy patients or patients with lung cancer are suppressed significantly by nonselective Cox inhibitors, including aspirin, and by Cox-2-selective inhibitors (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the majority of PGE 2 formed in vivo is derived from Cox-2 (24,25). Urinary PGE-M levels in healthy patients or patients with lung cancer are suppressed significantly by nonselective Cox inhibitors, including aspirin, and by Cox-2-selective inhibitors (25).…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58] In addition, increased prostaglandin E2 metabolite in the urine is found in women who are obese and is associated with an increased risk of postmenopausal breast cancer. 59,60 This could be a consequence of increased COX-2 levels in inflamed fat. Thus, smoldering WAT inflammation and low-grade systemic inflammation are inexorably coupled, and each perpetuates the other.…”
Section: Extended Impact Of the Inflamed Microenvironmentmentioning
confidence: 99%
“…This low grade, smoldering inflammation has been associated with cancer development and promotion [87]. Several inflammatory biomarkers are commonly increased in obese individuals and data suggests a positive correlation between their levels in blood (TNF-α; IL-6) [62] and urine (PGE 2 metabolites) [88] with development and/or progression of breast tumors. In the complex context of systemic inflammation, circulating chemokines are active not only in recruiting monocytes to adipose tissue, but also through the stimulation of macrophage proliferation in the fat pad [89] that contributes to a continuous positive feedback system for local WAT inflammation.…”
Section: Inflammation: the Emerging Link Between Obesity And Cancermentioning
confidence: 99%